Analysis of Temperature Controller in Thermal Chambers for Arbitrary References (LACCEI, 2024)
In the present work it is proposed to control the temperature of a thermoelectric module used in the construction thermal cameras for material characterization, including smart materials such as memory alloys shape among others. There are models that represent thermoelectric modules, where they are better represented by the output current in the thermoelectric module, in this work an amplifier controller model is used current and the respective model of the thermoelectric module and thermal chamber. This thermoelectric module set, current amplifier and thermal chamber is considered as a non-linear load (variable impedance to be controlled). To realize effective temperature control, a temperature controller in the thermoelectric module is designed in closed loop in such a way as to guarantee the desired temperature. As it is necessary to measure the temperature in the thermoelectric module or in the chamber, a thermistor type sensor is inserted, as it has a fast response when compared to other types of sensors. In the temperature controller analysis, different perturbations were considered as: ambient temperature between 15 and 35 degrees centigrade, temperature variation between -10 and 100 degrees centigrade, thermoelectric module impedance variation capability, delay disturbances produced on the thermistor response and the effect of the heatsink on temperature cooling. Results of the transient response analysis are presented showing the effectiveness of the proposed controller. Simulations are shown for sudden or arbitrary variations in temperature, and can even follow sinusoidal references, allowing evaluate that it is possible to control the amplifier set, thermoelectric module and thermal chamber, showing satisfactory results.